Adsorption of As(V) from Aqueous Solution on Chitosan-Modified Diatomite - Yang, Qintao (Int J Environ Res Public Health, 2020)
A novel chitosan (CS)-modified diatomite (Dt) was prepared by a simple mixture in the mass ratio to remove As(V) from aqueous solution in this research. The CS-modified Dt adsorbent was characterized by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and X-ray powder diffraction (XRD) analysis. The parameters to influence the adsorption of As(V) ion were studied under such conditions as kinetics, adsorption isotherm, and pH effect. The results revealed that adsorption of As(V) was initially rapid and the equilibrium time was reached after 40 min. The optimal value of the pH was 5.0 for better adsorption. The equilibrium data were well fitted to the Langmuir isotherm compared to the Freundlich isotherm, and exhibited the highest capacity and removal efficiency of 94.3% under an initial As(V) concentration of 5 mg/L. The kinetic data were well described by the pseudo-second-order model. In addition, 0.1 M NaOH has the best desorption efficiency of As(V) adsorbed on CS-modified Dt, and the removal efficiency of As(V) was still higher than 90% when after six adsorption-desorption cycles. These results showed that the CS-modified Dt could be considered as a potential adsorbent for the removal of As(V) in aqueous solution.